Novel biphenyl-substituted 1,2,4-oxadiazole ferroelectric liquid crystals: synthesis and characterization - Subrao, Mahabaleshwara; Potukuchi, Dakshina Murthy; Sharada Ramachandra, Girish; Bhagavath, Poornima; Bhat, Sangeetha G.; Maddasani, Srinivasulu (Beilstein Journal of Organic Chemistry, 2015)
Two novel series of unsymmetrically substituted 1,2,4-oxadiazole viz., R.Ox.C*Cn compounds are synthesized and characterized. An optically active, (S)-(+)-methyl 3-hydroxy-2-methylpropionate is used to introduce a chiral center in the molecule. A biphenyl moiety prepared by Suzuki coupling reaction is directly attached to the oxadiazole core at C-5 position. Investigations for the phase behavior revealed that the series with a benzyl group on one end of the oxadiazole core exhibits an 1D orthogonal smectic-A phase while the second series with dodecyl flexible end chain shows orthogonal smectic-A and tilted chiral smectic-C (SmC*) phases over a wide range of temperatures. The smectic-C phase exhibits ferroelectric (FE) polarization switching. The mesomorphic thermal stabilities of these compounds are discussed in the domain of the symmetry and the flexibility of the alkyloxy end chain length attached to the chiral center.
Keywords: 3,5-disubstituted-1,2,4-oxadiazoles; ferroelectric switching; mesomorphism; optical textures; SmC* phase; spontaneous polarization; Suzuki coupling